p53 Recruitment of CREB Binding Protein Mediated through Phosphorylated CREB: a Novel Pathway of Tumor Suppressor Regulation - Giebler, Holli A. (American Society for Microbiology, 2000)
CREB binding protein (CBP) is a 270-kDa nuclear protein required for activated transcription of a large number of cellular genes. Although CBP was originally discovered through its interaction with phosphorylated CREB (pCREB), it is utilized by a multitude of cellular transcription factors and viral oncoproteins. Both CREB and the tumor suppressor p53 have been shown to directly interact with the KIX domain of CBP. Although coactivator competition is an emerging theme in transcriptional regulation, we have made the fortuitous observation that protein kinase A-phosphorylated CREB strongly enhances p53 association with KIX. Phosphorylated CREB also facilitates interaction of a p53 mutant, defective for KIX binding, indicating that CREB functions in a novel way to bridge p53 and the coactivator. This is accomplished through direct interaction between the bZIP domain of CREB and the amino terminus of p53; a protein-protein interaction that is also detected in vivo. Consistent with our biochemical observations, we show that stimulation of the intracellular cyclic AMP (cAMP) pathway, which leads to CREB phosphorylation, strongly enhances both the transcriptional activation and apoptotic properties of p53. We propose that phosphorylated CREB mediates recruitment of CBP to p53-responsive promoters through direct interaction with p53. These observations provide evidence for a novel pathway that integrates cAMP signaling and p53 transcriptional activity.